Faktor-faktor yang berhubungan dengan kinerja pegawai administrasi rumah sakit di era new normal - Ellen Deivi Tamuntuan; Starry Homenta Rampengan; Oksfriani Jufri Sumampouw; Aaltje Elleb Manampiring (DiscoverSys Inc., 2021)
Background: Administrative employees as non-health workers in hospitals must provide excellent service so that organizational goals can be achieved, even though there are changes in the employee work system in this new normal era. Employee performance can be determined by factors related to performance, namely work discipline, motivation, leadership style, and work environment. This study aims to analyze the factors related to the performance of the administrative staff of the Ratatotok Buyat Central General Hospital (RSUP) in the new normal era.Methods: This study is an analytical study with a cross-sectional approach. This research was conducted at Ratatotok Buyat Hospital in May-June 2021. The research sample consisted of 50 respondents. The research instrument is a questionnaire that has been tested for validity and reliability—research data obtained through closed interviews. The data obtained were analyzed by univariate, bivariate, and multivariate. We used bivariate analysis using Pearson correlation test and multivariate analysis using multiple linear regression, with =0.05.Results: The results of this study indicate that the majority of the respondents are female (58%), aged 20-35 years (62%), have undergraduate education (72%), and have worked 6-10 years (52%). In addition, the results obtained in this study are work discipline, work motivation, leadership style, and work environment, p <0.05. The most influential factor on the performance of the administrative staff of Ratatotok Buyat Hospital is the work discipline variable (B=0.520). This study also obtained an R-square value of 0.661, which means work discipline, work motivation, leadership style, and work environment influence 66.1% on performance.Conclusion: There is a significant and positive relationship between work discipline, work motivation, leadership style, and work environment with the performance of administrative employees. The most influential variable is work discipline. Latar belakang: Pegawai administrasi sebagai tenaga non kesehatan di rumah sakit harus mampu memberikan pelayanan prima agar tujuan organisasi dapat tercapai, meskipun terdapat perubahan pada sistem kerja pegawai di era new normal ini. Kinerja pegawai dapat ditentukan oleh faktor-faktor yang berhubungan dengan kinerja yaitu disiplin kerja, motivasi, gaya kepemimpinan dan lingkungan kerja. Tujuan penelitian ini yaitu untuk menganalisis faktor-faktor yang berhubungan dengan kinerja pegawai administrasi Rumah Sakit Umum Pusat (RSUP) Ratatotok Buyat di era new normal.Metode: Penelitian ini merupakan penelitian analitik dengan pendekatan potong lintang. Penelitian ini dilaksanakan di RSUP Ratatotok Buyat pada bulan Mei-Juni 2021. Sampel penelitian berjumlah 50 responden. Instrumen penelitian yaitu kuesioner yang telah diuji validitas dan reliabilitas. Data penelitian diperoleh melalui wawancara tertutup. Data yang diperoleh dianalisis secara univariat, bivariat dan multivariat. Analisis bivariat menggunakan uji korelasi pearson dan analisis multivariat menggunakan uji regresi linear berganda, dengan ?=0,05.Hasil: Hasil penelitian ini menunjukkan bahwa responden paling banyak berjenis kelamin perempuan (58%), berusia 20-35 tahun (62%), berpendidikan sarjana/S1 (72%) dan masa kerja 6-10 tahun (52%). Selain itu hasil yang diperoleh dalam penelitian ini yaitu disiplin kerja, motivasi kerja, gaya kepemimpinan dan lingkungan kerja nilai p<0,05. Faktor yang paling berpengaruh terhadap kinerja pegawai administrasi RSUP Ratatotok Buyat yaitu variabel disiplin kerja (B=0,520). Diperoleh juga dalam penelitian ini nilai R2 sebesar 0,661 yang berarti disiplin kerja, motivasi kerja, gaya kepemimpinan dan lingkungan kerja memiliki pengaruh sebesar 66,1% terhadap kinerja.Kesimpulan: Terdapat hubungan bermakna dan positif antara disiplin kerja, motivasi kerja, gaya kepemimpinan dan lingkungan kerja dengan kinerja pegawai administrasi. Variabel yang paling berpengaruh yaitu disiplin kerja.